Balinese Karawitan Arts as a Media for Character Education and Preservation of Balinese Cultural Arts - Ni Wayan Masyuni Sujayanthi; Ni Putu Hartini (Institut Seni Indonesia Denpasar, 2023)
The negative impact of Covid-19 on children's character development calls for activities to restore social interaction that affects attitudes and behavior through Balinese Karawitan Art. The aim of such activities is to improve concentration and social interaction skills by applying the value of moral education in participating in Balinese Karawitan Arts activities. The implementation of character education values provides a correlation to children's growth and development using the mirror of effect theory, which refers to a person's character being influenced by his environment. The method used is a descriptive method by describing the phenomenon of the impact of Covid-19 as it affects the social interaction of children. Data collection was carried out by observation and interviews, the results of the research show that participating in Balinese Karawitan Arts activities at Sanggar Kertha Jaya brought positive changes to children's growth and development because, in addition to mastering Balinese gamelan techniques, the activities indirectly provided character education in an effort to instill the values of attitude and intelligence in thinking and appreciation. Recommendations: create activities that are able to increase social interaction while still implementing health protocols, especially in the arts that can shape the character of the nation's young generation.